Palladium-catalyzed regio- and stereoselective synthesis of aryl and 3-indolyl-substituted 4-methylene-3,4-dihydroisoquinolin-1(2H)-ones - Nori, Valeria; Arcadi, Antonio; Carlone, Armando; Marinelli, Fabio; Chiarini, Marco (Beilstein Journal of Organic Chemistry, 2020)
Cascade cyclocarbopalladation of the readily available aryl/alkyl-substituted propargylic amides containing an aryl iodide moiety, followed by Suzuki–Miyaura coupling with arylboronic acids, allowed an efficient regio- and stereoselective synthesis of tetrasubstituted 4-methylene-3,4-dihydroisoquinolin-1(2H)-ones. Moreover, cascade cyclocarbopalladation, followed by the reaction with 2-alkynyltrifluoroacetanilides, accomplished a double cyclization to afford challenging 4-methylene-3,4-dihydroisoquinolin-1(2H)-ones bearing a 3-indolyl substituent through aminopalladation/reductive elimination.
Keywords: alkynylanilines; arylboronic acids; indoles; isoquinolinones; palladium